Should spirituality be included in entrepreneurship education program curriculum to boost students’ entrepreneurial intention? - Hadi, Sutarto; Abbas, Ersis Warmansyah; Rajiani, Ismi (Frontiers in Education, 2022)
Spirituality is now encountering popularity because of both the physical and mental advantages acquired in the field of entrepreneurship. Independent of its more philosophical measurement, changes owing to spirituality has been distinguished in people's mental and standards of conduct. It is in this setting that this investigation examines the qualities related with university students, looking to explicitly comprehend the separate individual ascribes or the psychological and cognitive inclinations. This is because the academic writing affirms that most entrepreneurs possess typical psychological and cognitive physiognomies. The aftereffects of this investigation exhibit those students who participate in spirituality rituals show an inclination towards or reinforcing of the mental and psychological credits usually connected with an entrepreneurial profile. In this way the examination recommends that on the off chance that entrepreneurial behaviour is a priority to boost economic growth, spirituality ought to be coordinated as a mandatory subject into general instruction from the primary school onwards. The results of this exploration could be a model for Indonesian government currently like other countries all over the world is trying to find the best model for Entrepreneurship Education Program (EEP).